Alat Tangkap Ikan dan Tangkapannya di Selat Haruku Kabupaten Maluku Tengah, Maluku - Abdul Rahim Lestaluhu (CV. Multi Kreasi Media, 2022)
The Straits of Haruku is the water between Ambon Island and Haruku Island. In these waters, various fishing gear are operated by fishermen from coastal countries from both islands. This study aims to find out the fishing gear operated in the Haruku Strait and its catch. The fisherman sample was determined deliberately, taking into account that the fisherman's respondents were fishermen who fished in the Haruku Strait. The unavailability of statistical data on fishermen who go to sea in the Haruku Strait, so sampling is carried out using convenience techniques (hapzard or accidental). As a result of the study, the fishing gear used was vertical line, tuna long line, mini purse seine, boat lift net, and fish aggregation device/FAD. The catch is diverse, 20 types, consisting of 6 types of small pelagic fish, 4 types of large pelagic fish, and 10 types of demersal fish. Small pelagic fish such as momar (Decapterus macrosoma), kawalinya (Selar crumenopthalmus), lema (Rastrelliger sp.), make (Sardinella sp.), puri (Stolepharus sp.), and wasaula (Dipterygonotus sp.). Large pelagic fish such as komu (Euthynnus affinis), skipjack (Katsuwonus pelamis), tatihu (Thunnus albacares), tenggiri (Scomberomorus sp.), and bubara (Caranx ignobilis). Demersal fish such as lalosi (Caesio sp.), piskada (Sphyraena sp.), gaca (Lutjanus sp.), sikuda (Lethrinus sp.), garopa (Epinephelinae spp.), silapa (Aphareus rutilans), salmaneti (Parupeneus sp.), tatu (Odanus sp.), and mata bulan (Priacanthus sp.). The catch of small pelagic fish is 98,958 kg / year, large pelagic fish is 1,091 kg / year, and demersal fish is 3,367 kg / year.